Development of Geoladder Polygon Board Game Learning Media to Enhance Critical Thingking Skills of 4th Grade Students - Kinanti, Dian Putri; Kusuma, Dani (Jayapangus Press, 2025)
This study aims to develop and evaluate the effectiveness of the GeoLadder Polygon Board Game as an innovative learning medium to enhance the critical thinking skills of fourth-grade elementary students, specifically in polygon geometry. Using a Research and Development (R&D) approach based on the ADDIE model (analysis, design, development, implementation, and evaluation), the board game was systematically created and tested for educational use. The GeoLadder Polygon Board Game combines mathematical content with critical thinking exercises in a collaborative, interactive format, offering a hands-on and engaging alternative to traditional lectures. Validation by subject matter experts and media specialists yielded high feasibility scores: 88.3% for content accuracy and 96.6% for media quality, confirming the product’s suitability for classroom use. Field implementation at SD Negeri 02 Jampiroso with a purposive sample of students showed significant improvement in critical thinking skills, supported by a paired t-test (p < 0.05) and an N-Gain score of 0.83, indicating high learning effectiveness. Qualitative data from classroom observations and student questionnaires also indicated increased motivation, engagement, and collaboration. These results suggest that board games can effectively address challenges in understanding abstract mathematical concepts while fostering higher-order cognitive skills. The study recommends broader use of the GeoLadder Polygon Board Game in elementary mathematics curricula and encourages further innovation, including digital integration, to enhance accessibility and adaptability in diverse learning environments.